1997
DOI: 10.1093/oxfordjournals.aje.a009200
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Placental Infection with Plasmodium falciparum and Malaria Morbidity during the First 2 Years of Life

Abstract: In areas endemic for malaria, pregnant women frequently present with a placenta that has been parasitized by Plasmodium falciparum, an infection associated with a reduction in the birth weight of the offspring. However, the impact of placental infection on malaria-related morbidity during the infant's first years of life has not been investigated. Between 1993 and 1995, 197 children in southern Cameroon were followed weekly clinically and monthly parasitologically. The dates of first positive blood smear and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
134
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 14 publications
16
134
1
1
Order By: Relevance
“…[34][35][36][37] Although this study was not able to identify the major factor that leads to the susceptibility to the first malaria infection, the relationship between longer time to the first malaria infection and subsequent lymphocyte proliferation we observed may reflect the overall good status of cellular immunity.…”
Section: Discussionmentioning
confidence: 74%
“…[34][35][36][37] Although this study was not able to identify the major factor that leads to the susceptibility to the first malaria infection, the relationship between longer time to the first malaria infection and subsequent lymphocyte proliferation we observed may reflect the overall good status of cellular immunity.…”
Section: Discussionmentioning
confidence: 74%
“…The fact that no immunological effects were observed in acute PM suggests that a certain amount of PM exposure time is required for the immunological effects to occur, and demonstrates the value of analyzing by histological group. FOXP3 1 regulatory T-cell induction could explain why PM infected children are more susceptible to malaria infections in early life [4,5], since we have shown that those with higher ex vivo Treg levels are more susceptible to subsequent infections [42]. Indeed, a recent study shows that malaria exposure in utero can lead to immune tolerance induction in some newborns characterized by a decrease in the number of individuals mounting a pro-inflammatory response and increased numbers with malaria Ag driven IL-10 production [43].…”
Section: Cd25mentioning
confidence: 99%
“…PM leads to poor fetal outcomes, including premature delivery and low birth weight. Furthermore, infants born of malaria infected mothers/ placentas are more susceptible to malaria in the first few years of life than those whose mothers were not infected, through unknown mechanisms [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…There have also been concerns about whether prevention of malaria in the mother will render the newborn and young infant more susceptible to malaria infection, though limited evidence to date argues against this. 49 Finally, we limited our analysis to women in their first and second pregnancies because malaria-associated LBW is primarily a problem of primigravidae and secundigravidae in areas of high malaria transmission. In addition, most of the available published data on the efficacy of SP in reducing rates of placental malaria in HIV-positive compared with HIV-negative women focuses on primigravidae and secundigravidae.…”
Section: Resultsmentioning
confidence: 99%